INDIVIDUAL CHARACTERISTICS, FINANCIAL LITERACY AND ABILITY IN DETECTING INVESTMENT SCAMS - Chariri, Anis; Sektiyani, Wibowati; Nurlina, Nurlina; Wulandari, Richa Wahyu (JURNAL AKUNTANSI DAN AUDITING, 2018)
This study aims to explore important indicators applicable for the early detection of investment scams and to investigate the effect of age, education and financial literacy on the ability to detectinvestment scams. Data were collected using a questionnaire survey with respondents inSemarang, Indonesia. A total of 311 respondents completed the questionnaires, for a 62.2%response rate, but only 304 questionnaires were usable. Confirmatory factor analysis was used toverify the indicators of investment scams, and a regression model was then employed to analyzethe data. The findings show five main indicators applicable for early detection of investmentscams: a) investments with unreasonably-high returns, b) investment involving salespeople thattend to force potential investors to make an immediate decision about the investment, c)investments without reasonable underlying cores of business, in accordance with principles offairness and prudence in financial investment sectors, d) investments with no clear explanationon how the investment funds are managed, and e) investments without any information on thestructure of management, ownership, and business, and the address of the companies. Finally,the finding shows that the level of individual financial literacy positively affects the ability todetect investment scams. However, age and education do not affect the ability to detectinvestment scams.